Anti‐jamming scheme for GPS receiver with vector tracking loop and blind beamformer. Issue 19 (1st September 2014) - Li, Qiang; Xu, Dingjie; Wang, Wei; Wang, Xianpeng; Han, Zifa
Abstract : A novel scheme with an antenna array and a vector delay lock loop (VDLL) is proposed for improving the anti‐jamming capability of the global positioning system (GPS) receiver. The VDLL is used to supply reference information relying on the unique structure of the coarse/acquisition code for blind beamformers. A spectral self‐coherent restoral with a sparse constraint algorithm is presented to suppress interference and preserve the satellite signal without the direction of arrival of the satellite signal. Simulation results show that the proposed method can not only successfully suppress interference but also ensure the reliability of the VDLL in the presence of interference.